2019
DOI: 10.1136/heartjnl-2019-314931
|View full text |Cite
|
Sign up to set email alerts
|

Weight change and the risk of incident atrial fibrillation: a systematic review and meta-analysis

Abstract: BackgroundThe prevalence of obesity is increasing globally and this could partly explain the worldwide increase in the prevalence of atrial fibrillation (AF), as both overweight and obesity are established risk factors. However, the relationship between weight change and risk of incident AF, independent of starting weight, remains uncertain.MethodsMEDLINE, Embase, Pubmed, Web of Science, Cochrane Central R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…Our finding that weight loss was not associated with AF risk is in line with the results of several prior studies 9,12–15,26 . An intensive lifestyle intervention study that included individuals with type 2 diabetes reported no association between weight loss and risk of AF 15 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that weight loss was not associated with AF risk is in line with the results of several prior studies 9,12–15,26 . An intensive lifestyle intervention study that included individuals with type 2 diabetes reported no association between weight loss and risk of AF 15 .…”
Section: Discussionsupporting
confidence: 91%
“…8 The mean weight change in that study was 4%, A meta-analysis showed an association between a weight gain of 5% and increased risk of AF. 26 Differences in studied populations and age of onset of AF might explain the differences between the results of our study compared to the previous studies.…”
Section: Weight Change Cohortcontrasting
confidence: 79%
See 1 more Smart Citation
“…Previous systematic reviews have focused on individual predictors for AF, 58 , 59 on AF as a risk factor for other outcomes, 60 , 61 or on risk models for adverse outcomes in AF patients. 62 , 63 However, to our knowledge, this is the first systematic review and meta-analysis on performance of incident AF risk prediction models, and the first with a focus on such risk models validated in and applicable to the community.…”
Section: Discussionmentioning
confidence: 99%
“…In a propensity‐matched cohort study evaluating 5044 patients, there was an AF incidence rate of 0.8% versus 2.9% after metabolic surgery compared with conventional treatment 92 . Substantial weight loss seems to be a key factor in reduction of incident AF or reversal, and studies have shown modest weight loss to be less successful 93,94 …”
Section: Efficacy Of Metabolic Surgerymentioning
confidence: 99%